The importance of plant growth-promoting rhizobacteria to increase air pollution tolerance index (APTI) in the plants of green belt to control dust hazards - Najafi Zilaie, Mahmood; Mosleh Arani, Asghar; Etesami, Hassan (Frontiers in Plant Science, 2023)
Dust causes adverse effects on the physiological and biochemical characteristics of plants and limits their use in the development of the green belt. Air Pollution Tolerance Index (APTI) is an important tool to screen out plants, based on their tolerance or sensitivity level to different air pollutants. The aim of this study was to investigate the effect of two plant growth-promoting bacterial strains (Zhihengliuella halotolerans SB and Bacillus pumilus HR) and their combination as a biological solution on APTI of three desert plant species of Seidlitzia rosmarinus, Haloxylon aphyllum and Nitraria schoberi under dust stress (0 and 1.5 g m-2 30 days-1). Dust caused a significant decrease of 21% and 19%, respectively, in the total chlorophyll of N. schoberi and S. rosmarinus, an 8% decrease in leaf relative water content, a 7% decrease in the APTI of N. schoberi, and a decrease of 26 and 17% in protein content of H. aphyllum and N. schoberi, respectively. However, Z. halotolerans SB increased the amount of total chlorophyll in H. aphyllum and S. rosmarinus by 236% and 21%, respectively, and the amount of ascorbic acid by 75% and 67% in H. aphyllum and N. schoberi, respectively. B. pumilus HR also increased the leaf relative water content in H. aphyllum and N. schoberi by 10% and 15%, respectively. The inoculation with B. pumilus HR, Z. halotolerans SB and the combination of these two isolates decreased the activity of peroxidase by 70%, 51%, and 36%, respectively, in N. schoberi, and 62%, 89%, and 25% in S. rosmarinus, respectively. These bacterial strains also increased the concentration of protein in all three desert plants. Under dust stress, H. aphyllum had a higher APTI than the other two species. Z. halotolerans SB, which had been isolated from S. rosmarinus, was more effective than B. pumilus HR in alleviating the effects of dust stress on this plant. Therefore, it was concluded that plant growth-promoting rhizobacteria can be effective at improving the mechanisms of plant tolerance to air pollution in the green belt.